Biodegradable nanoparticle-mediated K-ras down regulation for pancreatic cancer gene therapy. Issue 10 (14th March 2015) - Yang, Chengbin; Hu, Rui; Anderson, Tommy; Wang, Yucheng; Lin, Guimiao; Law, Wing-Cheung; Lin, Wei-Jen; Nguyen, Quoc Toan; Toh, Hui Ting; Yoon, Ho Sup; Chen, Chih-Kuang; Yong, Ken-Tye
<x xml:space="preserve">Abstract</x> Biodegradable nanoparticle-mediated K-ras siRNA delivery has shown inhibition of cell proliferation, migration and invasion in pancreatic cancer cells.